Can the Effects of Religion and Spirituality on Both Physical and Mental Health be Scientifically Measured? An Overview of the Key Sources, with Particular Reference to the Teachings of Said Nursi - Turner, Mahshid (Journal of religion and health, 2015)
Within Western secular societies, everything has to be substantiated by empirical evidence; this means it has to be quantifiable and measurable. Research, particularly quantitative research, then, is the criterion by which everything, including religion, is either accepted or rejected. The separation of religion from science began with the Renaissance, the Reformation and the advent of the Enlightenment. It was perceived that religion did not match the language of science and that there was no logical proof or empirical evidence for the existence of God. Religion therefore, due to its inability to be measured and quantified, has since been largely marginalised. In recent times, in order to integrate ‘religion’ into everyday life, attempts have been made to argue and bring in scientific proof for the effectiveness of religion for improved health and well-being. The psychiatrist Harold Koenig has been one of the key people whose collation of research evidence has shown that religion has a positive effect on both physical and mental health. By looking firstly at the definitions of religion and spirituality and then discussing various opinions from both secular and religious perspectives, including those of Said Nursi, this paper aimed to determine whether religion and spirituality can indeed be measured.